Cracking the Book Value Mystery: Understanding Earning Per Share, Price Earning Ratio, and Operational Efficiency in IDX80 Enterprises Indonesia - Bustani, Bustani (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This study aims to elucidate the determinants of book value by investigating the effects of earnings per share (EPS), price-to-earnings (PER) ratios, and operational efficiency among companies listed in the IDX80 index from 2021 to 2023. Design/methodology/approach: The research utilizes a quantitative approach with an explanatory design, analyzing secondary data from the financial reports of 80 companies. Variables like EPS, PER, BV, and NPM are assessed using the Partial Least Squares (PLS) method via SmartPLS to uncover their relationships in the Indonesian capital market. Research Findings: Key findings highlight the significant impact of EPS on share valuation reflected in book value (BV) and the mediating role of NPM in this relationship. The study underscores the complexity of using PER alone to evaluate company worth within the IDX80 index, emphasizing the need for further exploration to enhance investment strategies and financial decision-making. Theoretical Contribution/Originality: This study enhances understanding of equity valuation in Indonesia's capital market by analyzing how EPS, PER ratios, and operational efficiency influence companies in the IDX80 index from 2021 to 2023. It integrates theoretical frameworks like signalling theory and mediation via NPM, showing that EPS significantly impacts share valuation through NPM. The research underscores limitations of using PER exclusively to evaluate company worth, emphasizing the intricate nature of stock valuation in the IDX80 index. Future studies should delve deeper into these factors to improve investment strategies and financial decision-making.